Selecting and Assessing Underutilized Trees for Diverse Urban Forests: A Participatory Research Approach - Hilbert, Deborah R.; Koeser, Andrew K.; Roman, Lara A.; Andreu, Michael G.; Hansen, Gail; Thetford, Mack; Northrop, Robert J. (Frontiers in Ecology and Evolution, 2022)
Urban forests provide critical environmental benefits, but the resilience of these socio-ecological systems to stresses like pest and disease outbreaks relies on tree health and diversity. Yet low species diversity continues to be a challenge in urban forest management. Using a participatory research approach in central Florida (United States), we selected and tested underutilized native tree species (Celtis laevigata Willd., Ilex vomitoria Aiton, Taxodium ascendens Brongn., Ulmus alata Michx., and Viburnum obovatum Walter) in two urban settings (streetscape and park) in four communities (n = 200). Our collaborative process was organized into five steps, including a two-year monitoring period to assess mortality and health through establishment. At the end of the trial, 156 trees survived with annual mortality rates differing by species and plot type. Taxodium ascendens had the highest annual mortality of the five species trialed. Additionally, trees in street plots had lower mortality compared to trees in park plots. Overall, U. alata and V. obovatum showed the greatest potential in central Florida urban settings. Our tree selection process can guide others who want to create forward-thinking and diverse planting lists. Furthermore, this project demonstrates that co-production of knowledge involving members of local municipalities, practitioners, and researchers can be an effective strategy for selecting and testing underutilized tree species.